Resilience: A New Consideration for Environmental Remediation in an Era of Climate Change. Issue 1 (17th December 2015) - O'Connell, Shannon; Hou, Deyi
Abstract : There has been a growing movement within the environmental industry to develop more sustainable approaches in environmental remediation. These have generally included carbon footprint analysis, life cycle assessment, and best management practices to reduce the overall net environmental, social, and economic impacts of investigation and remediation activities. One of the foundational reasons net environmental impacts are currently evaluated is to identify and, subsequently, reduce contributions to climate change, primarily greenhouse gas emissions. While this trend toward sustainability and reduction in impact to the global environment is both important and admirable, the approach to remediation design and long‐term planning now needs to evolve further to better incorporate climate resilience into sustainable remediation design and implementation: designing remediation solutions that account for the projected impacts of climate change, as well as have the capacity to adapt to changing conditions. As a global population, we are now beyond the point of being able to prevent climate change and instead need to plan for adapting to it. In remediation, the effects of climate change create both risks and opportunities which should be considered during remedial design and long‐term planning. Responsible parties may see the push for—and management of—these considerations through their internal corporate risk management. The authors of this paper propose a simple framework for climate adaptation and resilience evaluations and plan development for remediation projects. ©2015 Wiley Periodicals, Inc.